OPTIMIZATION OF SIMULATION MODEL PARAMETERS FOR SOLIDIFICATION OF METALS WITH USE OF AGENT-BASED EVOLUTIONARY ALGORITHM - Kluska-Nawarecka, S.; Smolarek-Grzyb, A.; Byrski, A.; Wilk-Kołodziejczyk, D. (Computer Science, 2013)
The finite elements method (FEM) is currently widely used for simulation of thermal processes.However, one of still unresolved problems remains proper selection of mathematicalmodel parameters for these processes. As far as modelling of cooling casts in forms is concerned,particular difficulties appear while estimating values of numerous coefficients suchas: heat transport coefficient between metal and form, specific heat, metal and form heatconduction coefficient, metal and form density. Coefficients mentioned above depend not onlyon materials properties but also on temperature. In the paper the idea of optimalizationof simulation method parameters based on adaptive adjustment of curve representing simulationresult and result obtained in physical experiment is presented along with the ideaof evolutionary and agent-based evolutionary optimization system designed to conduct suchoptimizations. Preliminary results obtained with use of ABAQUS system available in ACKCYFRONET and software developed at AGH-UST conclude the paper.